Real-Time Imaging and Testing of Anarchy=0 Throughout the Universe - Hamidi, Nabil (My University, 2025)
I test anarchy=0 throughout the entire universe, and I find it to be true as a physical, observable, seen, testable, and measurable constant. The dataset helps me explain why it is the physical code of everything that is physical and measurable and verified by rigorous scientific testing. When I say the equation is physical, it simply means that it is physically observable everywhere, even beside, above, or beneath you. Anarchy=0 might be simply the ultimate code of why everyone and everything exists in the universe. It is the ultimate origin, I propose, of anything we talk about, describe, touch, hear, smell, and see in the universe. Thank you for reading the paper.